THE FEATURES OF DISTRIBUTION OF POLITICAL RADICALISM AND EXTREMISM IN THE YOUTH ENVIRONMENT OF UKRAINE - Васильчук, Є.О. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2013)
The reasons and features of distribution of political radicalism and extremism are considered in the youth environment of Ukraine. It is marked that over the crisis terms of the social becoming and development bring to appearance of informal associations of young people, in the environment of that alternative ideas are formed about politics, culture, economy, that can acquire the opposition radicalism colouring in course of time.